Non-fictional creativity on the margins of aesthetics and communication - Kosiuk, Oksana M. (My University, 2025)
Thus, (despite attempts to move to another level of information quality and closer to journalism), in documentary filmmaking we still find non-compliance with journalistic standards, manipulation and influence on consciousness, excessive imagery, and so on. Obviously, documentary and journalism are very similar, but not identical in nature. And this, as we were able to see, is a non-historical fact. The audience should be carefully prepared for such a statement, which should regulate the strategies of their own perception of information, depending on what is being viewed: a documentary or one of the genres of journalism. Our findings and conclusions can also be considered a field for future research and one of the priority areas for improving documentary and journalistic products.
Keywords: journalism; communication; science; fact; genre; documentary film; fiction; manipulation; information; propaganda; non-fiction; 366.637